Asymmetry and Spillover Effects in the North American Equity Markets - Giorgio Canarella; Sunil K. Sapra; Stephen K. Pollard (Kiel Institute for the World Economy (IfW), 2007)
In this paper we extend the standard shock spillover model of Bekaert and Harvey (1997), Baele (2003) and Ng (2000) to account for asymmetries of return and volatility spillover effects from the US equity market into Canada and Mexico. Unlike previous research, we model the conditional volatility of the returns in each of the three markets using the asymmetric power model of Ding, Granger and Engle (1993). The empirical results indicate that volatility spillover effects, but not mean spillover effects, exhibit an asymmetric behavior, with negative shocks from the US equity market impacting on the conditional volatility of the Canadian and Mexican equity markets more deeply than positive shocks.
Keywords: G15; C32; C53; F31; 330; APARCH; Asymmetric Spillovers; North American Stock Markets